Combating Attention Deficit Hyperactivity Disorder through the Integration of Multiple Intelligences - Jennifer Cady (The Advocate, 2012)
In recent years, millions of children have been diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). As a result, schools are ill-equipped to handle the distractive characteristics that often times accompany those diagnosed with ADHD. Through the use of the Muliple Intelligences, established by Howard Gardner, teachers can begin to construct lessons that meet the needs of all learners, but particularly those individuals diagnosed with ADHD.